Systematic review of chimney and periscope grafts for endovascular aneurysm repair. Issue 12 (9th October 2013) - Wilson, A.; Zhou, S.; Bachoo, P.; Tambyraja, A. L.
<x xml:space="preserve">Abstract</x> Background Conventional endovascular aneurysm repair (EVAR) needs a proximal aortic seal zone that is free from aortic branch vessels. The modified application of conventional EVAR devices using adjuvant chimney or periscope grafts is described as a pragmatic alternative to custom‐made fenestrated and branched endografts. This systematic review examined the application and outcomes of chimney or periscope grafts for aortic aneurysm. Methods A search was performed for all studies of chimney or periscope grafts for EVAR. Clinical details and outcome in terms of technical success, survival, freedom from endoleak and branch vessel patency were examined. Results Twenty‐four studies describing 234 patients who underwent EVAR with one or more chimney or periscope grafts for aortic branch vessels were identified. Most procedures were elective; only 62 (26·5 per cent) were performed urgently. There were 176 patients with an abdominal aortic aneurysm and 58 with a thoracic or thoracoabdominal aortic aneurysm. Three hundred and seventy‐six branch vessels were perfused. Twelve patients (5·1 per cent) died within 30 days of aneurysm repair. Twenty‐seven patients (11·5 per cent) developed a type I endoleak. After a mean(s.d.) follow‐up of 12(5) months, seven branch vessels stents had occluded. Conclusion These highly selected data support the potential value of chimney and periscope graft techniques for patients with challenging aortic aneurysm morphology. There is a lack of medium‐ and long‐term follow‐up data. Presented to the Annual Meeting of the British Society of Endovascular Therapy, Stratford‐upon‐Avon, UK, June 2012